2015
DOI: 10.16949/turcomat.71538
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of Prospective Elementary Mathematics Teachers' Regarding to Reflection Symmetry

Abstract: Bu çalışma ile ilköğretim matematik öğretmeni adaylarının simetri kavramına ilişkin kavram yanılgılarının ortaya konulması amaçlanmıştır. Araştırmanın katılımcıları, 2012-2013 öğretim yılı güz döneminde Kocaeli Üniversitesi Eğitim Fakültesi İlköğretim Matematik Öğretmenliği programının dördüncü sınıfında öğrenim görmekte olan 28 öğretmen adayından oluşmaktadır. Betimsel bir araştırma niteliğindeki bu çalışmanın verileri, araştırmacılar tarafından hazırlanan açık uçlu bir test ile elde edilmiştir. Verilerin ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…This provides the students to develop the idea that if the closed shape is cut into two equal parts, one of its part is the reflection of the other part. In the study of Hacısalihoğlu-Karadeniz et al (2015) they pointed out that the candidate teachers had the same misconceptions and this would also affect their students when they became teachers. Likewise, Son (2006) stated that the teacher candidates had some misconceptions such as thinking a parallelogram has symmetry axis It was observed that the students fell into conceptual mistakes since they couldn't explore the connection between side and symmetry axis in regular polygons.…”
Section: R: Yes the Question Asks If There Are Horizontal Or Verticamentioning
confidence: 99%
See 1 more Smart Citation
“…This provides the students to develop the idea that if the closed shape is cut into two equal parts, one of its part is the reflection of the other part. In the study of Hacısalihoğlu-Karadeniz et al (2015) they pointed out that the candidate teachers had the same misconceptions and this would also affect their students when they became teachers. Likewise, Son (2006) stated that the teacher candidates had some misconceptions such as thinking a parallelogram has symmetry axis It was observed that the students fell into conceptual mistakes since they couldn't explore the connection between side and symmetry axis in regular polygons.…”
Section: R: Yes the Question Asks If There Are Horizontal Or Verticamentioning
confidence: 99%
“…These misconceptions are generally the mistakes such as finding the reflection axis (Kaplan & Öztürk, 2014;Hacısalihoğlu-Karadeniz, Baran, Bozkuş & Gündüz, 2015;Yavuzsoy Köse & Özdaş, 2009), slope reflection on axis, finding the image of the objects, specifying the equation of the distances between the object itself and its image (Yavuzsoy Köse, 2012) and defining the concept of reflection transformation (Hacısalihoğlu-Karadeniz, et al,2015). Son (2006) indicates that teacher candidates often confuse reflection and rotation in their work.…”
Section: Introductionmentioning
confidence: 99%
“…The Updated Secondary School Mathematics Teaching Program (MEB, 2013) anticipates that students make use of concrete experiences, intuitions, informal information that they have in their daily life in order to support conceptual learning. Considering that, teachers are expected to prepare environments where students are able to relate their existing knowledge to the new knowledge that they have access to (Hacısalihoğlu-Karadeniz et al 2015). Conceptual knowledge consists of the meanings underlying rules, generalizations, their relationships and operations (Bekdemir, Okur & Gelen, 2010).…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…In order for the concept of a subject to be fully acquired by a student, the definitions and properties of such concept are required to be completely and accurately explained (Küçük & Demir, 2009). Otherwise, it is reported that students tend to memorize the operations based on the concept and definitions; for that reason, more emphasis should be placed on conceptual learning in this process so as to overcome such difficulty (Hacısalihoğlu-Karadeniz et al 2015). In conclusion, the acquisition of something is indispensable in conceptual knowledge; on the other hand, procedural knowledge features how to use a concept or an operation and may overlook the reason underlying such concept or operation (Baki, 1997).…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation